2021
DOI: 10.1021/acsami.1c03775
|View full text |Cite
|
Sign up to set email alerts
|

Ag-Doped and Antibiotic-Loaded Hexagonal Boron Nitride Nanoparticles as Promising Carriers to Fight Different Pathogens

Abstract: Utilization of antibacterial components-conjugated nanoparticles (NPs) is emerging as an attractive strategy for combating various pathogens. Herein, we demonstrate that Ag/BN NPs and antibiotic-loaded BN and Ag/BN nanoconjugates are promising carriers to fight bacterial and fungal infections. Extensive biological tests included two types of Gram-positive methicillin-resistant Staphylococcus aureus strains (B8469 and MW2), two types of Gram-negative Pseudomonas aeruginosa strains (ATCC27853 and B1307/17), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…coli planktonic cells. This is consistent with previous reports that the pure BN nanoparticles have no noticeable effect against bacteria. , Consistent with previous studies of nanoconjugates loaded with gentamycin, the effect of GPBN against S. aureus appeared to be time- and concentration-dependent. , All tested concentrations were observed to be bactericidal against S.…”
Section: Results and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…coli planktonic cells. This is consistent with previous reports that the pure BN nanoparticles have no noticeable effect against bacteria. , Consistent with previous studies of nanoconjugates loaded with gentamycin, the effect of GPBN against S. aureus appeared to be time- and concentration-dependent. , All tested concentrations were observed to be bactericidal against S.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Therefore, it is possible that gentamicin- and PDA-modified BN nanoparticles can still prevent bacterial infection after a certain degree of drug release. It was previously reported that about 81% of non-covalently interacting antibiotics could be released on the surface of BN nanoparticles . Therefore, it can be expected that by studying the interaction form of antibiotics and BN, different release modes can be obtained to achieve drug burst release or the possibility of providing long-term protection of nanocarriers.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a different note, addressing the challenges associated with nosocomial infection has become one of the topmost priorities in the health sector. Establishing efficient antimicrobial coatings over the frequently touched surfaces has been considered to be an essential strategy to combat the spread of microbial pathogenesis in hospital and crowded environment . Antibiotics and other chemical disinfectants are commonly used for this purpose; , however, this approach often leads to the incidence of drug-resistant pathogens that are more harmful. , Conventionally, it is known that silver nanoparticles and ionic silver exhibit a high antimicrobial property even at ultralow concentrations. A recent study demonstrated that the propensity of microbial mutation is substantially less with ionic silver over silver nanoparticles and thereby highlighted the advantage of ionic silver .…”
Section: Introductionmentioning
confidence: 99%
“…According to GB5749-2006 (National hygienic standard for drinking water of China), the content of Ag + is less than 0.05 mg l −1 (0.463 μM). Long-term accumulation of Ag + may have massive influences on human health and the environment [11][12][13][14]. Therefore, it is essential for selective detection of Ag + in the environment and related pathologies in living systems.…”
Section: Introductionmentioning
confidence: 99%